If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8u-40=-4(u-5)
We move all terms to the left:
8u-40-(-4(u-5))=0
We calculate terms in parentheses: -(-4(u-5)), so:We get rid of parentheses
-4(u-5)
We multiply parentheses
-4u+20
Back to the equation:
-(-4u+20)
8u+4u-20-40=0
We add all the numbers together, and all the variables
12u-60=0
We move all terms containing u to the left, all other terms to the right
12u=60
u=60/12
u=5
| 8u-40=-4u(u-5) | | -12/19+3/8q=-17/57 | | 600=25x+10x | | -39=u/6 | | -22=5(y-5)-8y | | -5x+3(x+1)-4x=45 | | 3x-24-7×=2×+24+2× | | 5(x+2-7=32 | | 3(y−7)+5y=83(y-7)+5y=8 | | -8x+4(x+3)=-28 | | -2(3x-5)=5(x+3)+8 | | 17+8x=-5x-9 | | -33=-5w+3(w-5) | | 4v-v=6 | | (1a-5)+1a=19 | | 50x-50-20x=-20 | | -21.4=r-4.5 | | (A-5)+a=19 | | 12+30t=162 | | 3x+4+x+12=180 | | 4.5(j+5)=2/5 | | 7(5r-4)=-20+9r | | .75x+2=12 | | 2x/3+16/3=4x/2 | | 56=16x | | t-3483511=53927 | | 10+a^2/9=26 | | 9x=648 | | 6+27x-16x^2=16 | | 2=x=x-8 | | 3-4x=2×+11 | | 9x=567 |